Da política ao prato: investigando a matriz institucional na execução do PNAE com enfoque na agricultura familiar - Schabarum, Joseane Carla (2024)
The National School Feeding Program (PNAE) is a Brazilian public policy that aims to ensure healthy and adequate food for students in public schools in the country. A key feature of the PNAE is the incentive to purchase food directly from family farming. The general objective of this work is to analyze the process of institutionalization and effectiveness of article 14 of the Federal Law No 11.947/2009 of PNAE in selected municipalities in the Geographic Mesoregions of Paraense and Presidente Prudente, São Paulo. It is a longitudinal study with qualitative-quantitative, descriptive and analytical approach with approval of the ethics committee in research with human beings of Unioeste. For the quantitative data, secondary public access data available in the On-line Account Management System of the National Fund for the Development of Education (FNDE) was used To identify the family farming food products that were categorized into ten groups: fruits and derivatives, vegetables and derivatives, cereals and derivatives, tubers and derivatives, beans, eggs, meat, milk and derivatives, sugars and sweets and others, and another classification according to the NOVA classification of the Food Guide for the Brazilian Population in nature or minimally processed, processed culinary ingredients, processed food and ultra-processed food and beverages. According to the level of attendance of municipalities to article 14 of Law 11.947/2009 these were grouped according to the percentage destined for family agriculture category 1- 0% of the transfer; category 2 - 0.1% to 29.9%; category 3 - 30% to 39.9%; and category 4 - ≥ 40%. Interviews were conducted with the 43 actors involved in school feeding of five municipalities, two from the Mesorregião Geográfica Oeste Paranaense and three from the Mesorregião Geográficas Presidente Prudente of São Paulo. The interviews were recorded, then transcribed and analyzed with the technique of content analysis. The categories of analysis were preestablished according to the institutional matrix of Douglass North: "organizations", "formal rules", "informal rules", "enforcement" and "path dependence". The results found allowed to identify that the acquisitions of family farming are superior in the Mesorregión Geográfica Oeste Paranaense in all analyzed years, with with detaque for acquisitions ≥40%. The Presidente Prudente Mesoregion has a significant number of municipalities that do not acquire anything or do not reach the minimum percentage of 30% required by the law. Regarding the type of products from family farming in both mesoregions, mostly were natural and minimally processed foods of vegetable origin (vegetables and fruits). The West Paraná Mesoregion presented higher percentages of processed foods (baked, for example) and the total number of items provided, besides commercialization of organic food. With regard to content analysis, it was possible to verify that the organizations and the informal rules present important influence on the effectiveness in the acquisitions of food of the family agriculture. However, the formal rules did not prejudice the implementation of the PNAE. It is concluded that even years after the promulgation of Law 11.947/2009, many municipalities still do not meet the requirements set by article 14. The institutional matrix has total influence on this cumprimeiro or not, that is, municipalities where all elements interact mutually reached the provisions of the law.